Provoking the press : (MORE) magazine and the crisis of confidence in American journalism - Lerner, Kevin M., 1977- (Journalism in perspective: continuities and disruptions., 2019)
"(MORE): A Journalism Review was co-founded by J. Anthony Lukas, a star at the New York Times who felt that the rigors of daily journalism were stifling him and other journalists like him, and Richard Pollak, a former Newsweek media writer. From 1971 to 1978, they and their collaborators and successors produced a monthly magazine that addressed newsroom diversity, the relationship between the press and politicians, censorship, and other issues essential to ensuring the institution's vitality. In telling the story of (MORE) and its legacy, Kevin Lerner explores the power of criticism to reform and guide the institutions of the press that, in turn, influence public discourse"--